Strategi Hukum dan Penerapan Partisipasi Masyarakat dalam Penyelesaian Sengketa Batas Daerah di Sumatera Selatan - Iza Rumesten RS. (Fakultas Hukum Universitas Islam Indonesia, 2013)
The long conflict on the regional border causes loss to a country, especially in terms of economic, and threatens the defense and security of the country. The purpose of this study is to analyze and formulate the legal step that can be taken to resolve the regional border conflict resulting from the regional expansion and to formulate a model for the community participation in resolving the border conflict in their region. The method used in this research is legal normative by analyzing and studying the regulations of law related to the regional expansion and by studying and analyzing the legal materials used by each party conflicting to claim the border in dispute. The result of the research concludes that: First, the legal strategies that can be taken to resolve the border conflict can refer to the Law No. 12 of 2008 on Regional Government and the Regulation of the Minister of Home Affairs No. 76 of 2012 on the Guidelines on the Regional Border Confirmation and the last measure that can be taken is the settlement through the Constitutional Court. Second, the active involvement of the community in the region in dispute must be encouraged in each process of the regional expansion proposition.